Pollination by native bees achieves high fruit quantity and quality of highbush blueberry: a sustainable alternative to managed pollinators - Cortés-Rivas, Benito; Monzón, Víctor Hugo; Rego, Juliana Ordones; Mesquita-Neto, José Neiva (Frontiers in Sustainable Food Systems, 2023)
Sonication or buzz-pollination is a phenomenon by which a floral visitor, generally bees, vibrates flowers to extract pollen efficiently. Blueberry is one of the most relevant buzz-pollinated crops worldwide and Chile is the most important global producer of fresh blueberries during wintertime in the Northern Hemisphere. Non-buzzing bees, such as honeybees, may provide suboptimal services compared to bees capable of buzz-pollinate. The widely held contention that honey bees are inferior pollinators of blueberries drives the industry to place pressure on governments to allow bumblebee (Bombus terrestris) importation for pollination. However, the introduction of B. terrestris generates environmental problems in Chile by competing with and transmitting parasites to local bees. Despite some native Chilean bees being recently recognized as efficient pollen vectors of blueberry crops, no study has evidenced the influence of their visits on fruit yield. Therefore, we aimed to evaluate the performance of native Chilean floral visitors in relation to managed visitors to improve fruit quantity and quality of highbush blueberry. Per-visit pollination performance (fruit set and fruit quality) and visitation frequency were measured and the performance of buzzing behavior by flower visitors was evaluated in four cultivars grown in five blueberry orchards located in southern Chile. We found that fruit set and weight were highly influenced by floral visitor taxon. Some native bee species can greatly improve fruit set and fruit quality (greater weight) of the highbush blueberry cultivars. For instance, one single visit of C. occidentalis can increase fruit weight by a factor of 1.8 over that for an A. mellifera visit, however, visits of halictids and syrphids resulted in lower fruit set than unvisited flowers. However, we found that the occurrence of sonication behavior alone was not a predictor of higher fruit set and fruit weight of highbush blueberry cultivars. Consequently, the taxonomic recognition of floral visitors, ideally to the species level, is still needed to distinguish the most efficient fruit yield promoters of blueberry. The conservation of the biotic pollinators, especially native ones, would improve blueberry fruit quality and is likely to improve overall crop productivity.